1999
DOI: 10.1557/jmr.1999.0249
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sol-gel Pb(Zr0.53Ti0.47)O3films in the thickness range 0.25–10 μm

Abstract: Films of nominal composition Pb(Zr0.53Ti0.47)O3 (PZT) in the thickness range 0.25−10 μm have been fabricated on Pt/Ti/SiO2/Si substrates using a propanediol-based sol-gel route. The spun-on coatings were prefired at 350 and 600 °C between successive depositions before firing the multilayer stack at 700 °C for 15 min. The variations in crystallite orientation, microstructure, and dielectric and ferroelectric properties were determined as a function of film thickness. For a constant applied field of 150 kV cm−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 18 publications
8
22
0
Order By: Relevance
“…Therefore, piezoelectric thin/thick film technology may be a good low-cost alternative solution for high frequency transducer (100-200 MHz) designs. However, the only drawback to using these materials is their inferior piezoelectric properties when compared to bulk produced piezoceramics [42][43][44][45][46][47][48].…”
Section: Piezoelectric Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, piezoelectric thin/thick film technology may be a good low-cost alternative solution for high frequency transducer (100-200 MHz) designs. However, the only drawback to using these materials is their inferior piezoelectric properties when compared to bulk produced piezoceramics [42][43][44][45][46][47][48].…”
Section: Piezoelectric Thin Filmsmentioning
confidence: 99%
“…Chen et al [45] produced PZT thick films by a modified sol-gel process involving an acetic acid route. Kurchania and Milne [46] also fabricated PZT thick films using titanium di-isopropoxide bi-acetylacetonate as a precursor material. Finally, Zhou et al reported the development of PZT composite films [47], and the fabrication of microelectromechanical (MEMS) tonpilz transducers using modified sol-gel PZT films [48].…”
Section: Piezoelectric Thin Filmsmentioning
confidence: 99%
“…PZT thick films meet the requirements of the device miniaturization and integration [1]. Among the reported deposition methods [5][6][7][8][9][10][11][12], chemical solution deposition (CSD) has been widely used to deposit PZT thick films. PZT thick films are usually grown on Pt/Ti/SiO 2 /Si substrate, which show excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several Investigations have described that the piezoelectric coefficients ¾ 31 , d 31 and d 33 are dependent upon the piezoelectric film thickness. 1), 2) The film thickness dependence of electric properties exists in thickness range of less than 0.2¯m.…”
Section: Introductionmentioning
confidence: 99%